2019
DOI: 10.21608/javs.2019.62653
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement Of Pneumo-4 Vaccine Efficacy By Using Of Carbomere As An Adjuvant

Abstract: The present study aimed to prepare a combined inactivated pneumo-4 vaccine containing bovine viral diarrhoea, infectious bovine rhinotracheitis (IBR), parainfluenza-3(PI-3) and bovine respiratory syncytial virus (BRSV) adjuvanted with carbomer and compare the animal protection scope with its product mate Pneumo-4 adjuvanted alhydragel . Carbomer adjuvant stimulated higher levels and longer lasting antibody to pneumo-4 vaccine than vaccines of equivalent antigenic content containing aluminium hydroxide gel adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…When montanide oil (ISA 206) was used [ 16 , 34 ] as an adjuvant, they found that it had a large safety margin with higher neutralizing antibody titers for longer durations compared to the commercial vaccine since it can trap the antigen and release it over long periods and increase the physical presentation of the antigen. The Pneumo-4 vaccine adjuvanted with carbomer 0.5% [ 17 ] showed high potency with the stimulation of cellular immunity compared to the vaccine adjuvanted with aluminum hydroxide gel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When montanide oil (ISA 206) was used [ 16 , 34 ] as an adjuvant, they found that it had a large safety margin with higher neutralizing antibody titers for longer durations compared to the commercial vaccine since it can trap the antigen and release it over long periods and increase the physical presentation of the antigen. The Pneumo-4 vaccine adjuvanted with carbomer 0.5% [ 17 ] showed high potency with the stimulation of cellular immunity compared to the vaccine adjuvanted with aluminum hydroxide gel.…”
Section: Discussionmentioning
confidence: 99%
“…Ten Albino Swiss weaned mice weighing 10–15 g were used in running safety tests of the prepared vaccine formulae [ 17 ]. They were obtained, reared, and observed in the Laboratory Animals Department, Veterinary Serum and Vaccine Research Institute, Abbasia, Cairo, Egypt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation